Mid‐infrared supercontinuum covering 2.0–16 μm in a low‐loss telluride single‐mode fiber. Issue 2 (March 2017) - Zhao, Zheming; Wu, Bo; Wang, Xunsi; Pan, Zhanghao; Liu, Zijun; Zhang, Peiqing; Shen, Xiang; Nie, Qiuhua; Dai, Shixun; Wang, Rongping
Abstract : A low‐loss telluride fiber with double‐cladding structure is reported. The core glass is (GeTe4.3 )90 (AgI)10, the first cladding is (GeTe4 )90 (AgI)10 and the second cladding is Ge10 Sb10 Se80 . A broadband mid‐IR supercontinuum spectrum is generated from the 14‐cm‐long fiber pumped by a 7‐μm laser (∼150 fs, 1 kHz), covering the 2–16 μm fingerprint region, which can be adopted to detect all the greenhouse gas radiation. Abstract: A mid‐infrared (MIR) supercontinuum (SC) has been demonstrated in a low‐loss telluride glass fiber. The double‐cladding fiber, fabricated using a novel extrusion method, exhibits excellent transmission at 8–14 μm: < 10 dB/m in the range of 8–13.5 μm and 6 dB/m at 11 μm. Launched intense ultrashort pulsed with a central wavelength of 7 μm, the step‐index fiber generates a MIR SC spanning from ∼2.0 μm to 16 μm, for a 40‐dB spectral flatness. This is a fresh experimental demonstration to reveal that telluride glass fiber can emit across the all MIR molecular fingerprint region, which is of key importance for applications such as diagnostics, gas sensing, and greenhouse CO2 detection.